Effects of 28 days of beta-alanine and creatine supplementation on muscle carnosine, body composition and exercise performance in recreationally active females - Kresta, Julie Y (J Int Soc Sports Nutr, 2014)
BACKGROUND: The purpose of this study was to examine the short-term and chronic effects of β-ALA supplementation with and without creatine monohydrate on body composition, aerobic and anaerobic exercise performance, and muscle carnosine and creatine levels in college-aged recreationally active females. METHODS: Thirty-two females were randomized in a double-blind, placebo-controlled manner into one of four supplementation groups: β-ALA only (BA, n = 8), creatine only (CRE, n = 8), β-ALA and creatine combined (BAC, n = 9) and placebo (PLA, n = 7). Participants supplemented for four weeks included a loading phase for the creatine for week 1 of 0.3 g/kg of body weight and a maintenance phase for weeks 2–4 of 0.1 g/kg of body weight, with or without a continuous dose of β-ALA of 0.1 g/kg of body weight with doses rounded to the nearest 800 mg capsule providing an average of 6.1 ± 0.7 g/day of β-ALA. Participants reported for testing at baseline, day 7 and day 28. Testing sessions consisted of obtaining a resting muscle biopsy of the vastus lateralis, body composition measurements, performing a graded exercise test on the cycle ergometer for VO(2peak) with lactate threshold determination, and multiple Wingate anaerobic capacity tests. RESULTS: Although mean changes were consistent with prior studies and large effect sizes were noted, no significant differences were observed among groups in changes in muscle carnosine levels (BA 35.3 ± 45; BAC 42.5 ± 99; CRE 0.72 ± 27; PLA 13.9 ± 44%, p = 0.59). Similarly, although changes in muscle phosphagen levels after one week of supplementation were consistent with prior reports and large effect sizes were seen, no statistically significant effects were observed among groups in changes in muscle phosphagen levels and the impact of CRE supplementation appeared to diminish during the maintenance phase. Additionally, significant time × group × Wingate interactions were observed among groups for repeated sprint peak power normalized to bodyweight (p = 0.02) and rate of fatigue (p = 0.04). CONCLUSIONS: Results of the present study did not reveal any consistent additive benefits of BA and CRE supplementation in recreationally active women.